Effect of minimizing carrier irrigation on H2 conversion in trickle bed reactors during ex situ biomethanation. (December 2021) - Sieborg, Mads Ujarak; Jensen, Mads Borgbjerg; Jensen, Bjarke; Kofoed, Michael Vedel Wegener
Abstract: Biological methanation of renewable H2 and CO2 has been projected to have considerable potential in future energy systems by coupling power and gas energy infrastructures. A suitable technology to facilitate the biological methanation is the ex-situ trickle bed reactor in which a methanogenic biofilm produces CH4 from H2 and CO2 . Biofilm irrigation constitutes a critical element for reactor control and has previously been shown to both enhance and decrease reactor performances. In this study, an improvement in the H2 conversion rate of 53% was demonstrated when increasing the interval between sprinklings from 1 to 7 days. The results demonstrate a minimal requirement for nutrient supply to support biological activity and underline that carrier irrigation not only impairs H2 conversion at short-term due to increases in the mass transfer resistance, but also induces longer-term effects on process performance. Three potential mechanisms underlying the physicochemical and biological effects imposed by carrier irrigation are discussed. Graphical abstract: Unlabelled Image Highlights: Carrier irrigation was demonstrated to reduce H2 consumption rate. The H2 consumption rate increased by extending the interval between sprinklings. Sprinkling potentially influences the physicochemical H2 gas-liquid mass transfer. Sprinkling potentially affects the planktonic microbes and biofilm development.